The Impact of Personalized Guest Experiences on Customer Loyalty in the Hotels of Kolkata - Bharadwaj, Anindita; Bathla, Gaurav (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
This study explores the impact of personalized guest experiences on customer loyalty in hotels located in Kolkata, India. In today’s competitive hospitality landscape, customer loyalty is increasingly influenced by tailored services that cater to individual guest preferences. The research is grounded in the understanding that personalized experiences including customized services, communication, and attention to guest-specific needs can significantly enhance guest satisfaction and foster long term loyalty. The objectives of the study are threefold: to examine the demographic profile of guests visiting Kolkata’s hotels, to identify key factors influencing customer loyalty through personalization and to analyse the extent to which personalized guest experiences impact loyalty outcomes. A quantitative research design was adopted using a structured questionnaire as the primary data collection tool. The survey was distributed among hotel guests in Kolkata using convenience sampling, yielding 212 valid responses. Responses were measured on a 5-point Likert scale and analysed through descriptive statistics, factor analysis, and ANOVA. The findings reveal that personalized guest experiences such as tailored services,